Independent podcasts on the Apple Podcast platform in the streaming era - Berg, Freja Sørine Adler (MedieKultur: Journal of media and communication research, 2021)
This article investigates independent podcasts created outside traditional institutions (Markman, 2012) on the world’s largest podcast platform, Apple Podcasts, in the context of streaming media. Through a quantitative content analysis of 552 Danish podcasts, the study offers insights into independent podcasting, its medium grammar and content (Meyrowitz, 1998), and the conditions by which independent podcasters navigate in a liminal space between traditional radio and online participatory practices (Berry, 2016; Markman, 2012). The analysis shows that the predominant parts of independent podcasts are conversations and interviews about personal, self-reflective stories and mainstream hobbies such as football, films, and television. These podcasts are less time-consuming to produce than crafted audio (McHugh, 2016) about research-heavy topics. The oversupply of conversations and interviews about personal stories and mainstream hobbies further suggests that independent podcasters are influenced by the mainstreaming and commercialisation of podcasting, including streaming platforms such as Spotify and Amazon adding podcasts to their services, and podcast platforms such as the Danish paid subscription podcast platform Podimo, adopting the curated content distribution model known from Netflix.